Peran Perempuan dalam UMKM Pengolahan Kopi Nagari Koto Tuo, Kabupaten Tanah Datar - Afifah, Fayi; Syabena, Muhammad Farrel; Novita, Ninda (Universitas Galuh, 2026)
The role of women in Micro, Small, and Medium Enterprises (MSMEs) for coffee processing in Indonesia is highly significant, particularly in Nagari Koto Tuo, Tanah Datar, West Sumatra. This qualitative study aimed to identify their contributions and analyze the resulting socio-economic impacts. Nationally, of MSME actors are women; in Koto Tuo, most coffee brand owners are women who inherited their processing skills. Employing a census approach, the research involved 160 women MSME actors, with data analyzed using the Miles and Huberman model. Findings indicate women play a crucial role across four aspects: production, marketing, business management, and collaboration networks. This active involvement is driven by socio-cultural factors, economic necessity (acting as the main income source), and personal characteristics (thoroughness and diligence). Their participation yields positive impacts, including enhanced social status, financial independence, and community recognition. Ultimately, women in Koto Tuo are key drivers of family welfare, community development, and successfully challenge traditional gender perceptions.